Reframing Madrasas in Afghanistan: A Historical Analysis of Islamic Education and Societal Change - Samiullah Adel; Bhirawa Anoraga; Mahmud Salim; Mahmood Rahimi; Hazrat Shah Kayen (Jurnal Pendidikan Islam, 2026)
In global academic and policy discourse, madrasas in Afghanistan are often represented through securitized and reductionist frameworks that conflate Islamic education with extremism, obscuring their historical depth and educational diversity. This article seeks to reframe such narratives by examining the historical development of Afghan madrasas from the pre-modern period to the post-2001 era, situating them within broader trajectories of Islamic education and societal change. Employing a qualitative historical approach through a systematic review of scholarly literature, historical sources, and policy reports, the study analyzes madrasa institutions using an integrated framework that combines the sociology of knowledge, historical institutionalism, and Islamic educational concepts of tarbiyah, taʿlīm, and turāth. The findings show that Afghanistan historically functioned as a significant center of Islamic learning, particularly during the eighteenth and nineteenth centuries, sustained by locally embedded institutions and transnational scholarly networks. While critical junctures, most notably the Soviet invasion of 1979 and subsequent conflicts, reconfigured madrasa functions and politicized religious education, these transformations were contingent on structural disruption, state fragility, and conflict rather than inherent features of madrasa pedagogy. The study concludes that Afghan madrasas are adaptive, context-responsive educational institutions whose continuity and change can only be understood through historically grounded analysis. The findings have broader implications for Islamic education globally, highlighting the importance of historicizing madrasa traditions, resisting securitized interpretations, and recognizing Islamic educational institutions as enduring contributors to moral formation, social resilience, and educational reform in conflict-affected and post-conflict societies.